Analytical Estimation of Jitter for the MMPP-N Traffic Model - Hicham Magri; Mohamed Rachdi; Mohamed Azzouazi (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
Nowadays, consumers demand powerful and adequate communication techniques to meet their desires for communication and exchange. These techniques, such online chats, VoIP, video conferencing, and AR/VR services, require well-defined Quality of Service (QoS) properties, such as minimal transmission delay, high throughput, low inter-arrival time, and low packet delay variation. Among these, jitter is an important QoS parameter in IP networks that can affect the performance of real-time applications and services. In this paper, we provide an overview of jitter and relevant studies. We propose an analytical calculation of jitter for the MMPP-2 and MMPP-N traffic models and analyze the jitter behavior for voice traffic.